Determining Bandgap of Thermochromic Phosphor Films via Reflectance Measurements under Controlled Heating (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2024)
In this article, we present a method to determine the bandgap of a thermochromic phosphor film by simple reflectance measurements under controlled heating. The phosphor is illuminated by a light[1]emitting diode while being heated continuously. The reflected light is detected using a calibrated photodiode circuit based on an operational transconductance amplifier. We apply the Schuster[1]Kubelka-Munk function to deduce the absorbance over temperature and thus the bandgap. We show, for the first time, that the thermochromic phosphor's colour change follows Arrhenius's Law and therefore involves activation energy. We estimate the bandgap to be between 1.1 eV and 1.9 eV and find an activation energy of 46.67 ±1.6 kJ/mol. The simplicity of the approach will appeal to undergraduate teachers and students of physics and materials science. The technique can be used to investigate other thermochromic materials as well.